Hydrogen storage: Investigation of the elastic properties of Mg7NbH16 hydride - Y. Bouhadda; M. Bououdina; N. Fenineche; Y. Boudouma (Revue des Énergies Renouvelables, 2015)
Structural, mechanical and electronic structure properties of Mg7NbH16 were investigated using the norm-conserving pseudo-potentials and plane waves (PP-PW) within the general gradient approximation (GGA) in the frame of density functional theory (DFT). The computed equilibrium lattice constants are in excellent agreement with the available experimental and theoretical data. The elastic constants Cij of Mg7NbH16 were calculated for the first time. The Mg7NbH16 compound is found to be mechanically stable. The bulk modulus of single crystals has been derived using elastic constants. The results are discussed and compared with the calculated bulk modulus reported in the literature. The polycrystalline elastic moduli (namely: the shear modulus, Young's modulus, Poisson's ratio, Lamé's coefficients, sound velocities and the Debye temperature) were derived from the obtained single-crystal elastic constants. According to the obtained results, Mg7NbH16 can be classified as ductile material. The shear anisotropic factors and the elastic anisotropy are also discussed. A Debye temperature of 619 K was also determined using theoretical elastic constants.